Study on effect of boundary conditions on simulation of wind flow in mountainous area. Issue 1 (1st June 2022) - Yin, Yuan; Li, Yangsen; Lin, Ruizong; Liu, Zhiwei; Fu, Benzhao; Huang, Guo; Zhang, Hongjie
Abstract: The simulation analysis of wind flow in mountainous area can assist the design of the transmission line. The conventional square computational domain is not conducive for the condition of different wind directions. In this paper, a circular computational domain is proposed for the solution of wind flow in mountainous area in the condition of different wind directions. A square computational domain and a circular one are used to solve the wind flow around the standard hill model. The simulation accuracy of the circular computational domain is verified by the wind profiles at the windward slope, the top of the slope and the leeward slope.